Preparation of novel polyamine-type chelating resin with hyperbranched structures and its adsorption performance. Issue 2 (7th February 2018) - Chen, Youning; Zhao, Wei; Wang, Huan; Li, Yuhong; Li, Chenxi
Abstract : This paper explored the method of combining atom transfer radical polymerization (ATRP) technology and hyperbranched polymer principle to prepare the high capacity chelating resin. First, surface-initiated atom transfer radical polymerization (SI-ATRP) method was used to graft glycidyl methacrylate (GMA) on chloromethylated cross-linked styrene-divinylbenzene resin, and then the novel polyamine chelating resin with a kind of hyperbranched structure was prepared through the amination reaction between amino group of (2-aminoethyl) triamine and epoxy group in GMA. This resin had a selective effect on As(V) and Cr(VI) at a relatively low pH and can be used for the disposal of waste water containing As(V) and Cr(VI). It had a relatively strong adsorption effect on Cu(II), Pb(II), Cd(II) and Cr(III) and can be used for the disposal of heavy metal ion waste water. The finding was that, the adsorption capacity of resin on the studied heavy metal ions was higher than that of the chelating resin synthesized by traditional technology and also higher than that of the resin modified by ATRP technology and bifunctional chelator, indicating that the combination of ATRP and hyperbranched polymer concept is an effective method to prepare chelating resin with high capacity.